Numerical Study on Resistance Change Characteristics of Phase Change Materials - Yifang Su; Yihang Zhang; Kaifeng Lin; Guanjun Zhao; Qinzheng Yu; Zuoqi Hu; Xiongfei Tao (Advances in Materials Science and Engineering)
Phase change materials are a type of emerging materials whose states will change under certain conditions, which then lead to changes in resistance. To study the characteristics of the phase change materials, a numerical simulation model of the resistive change unit based on the finite element method and the classic nucleation/growth theory is established, while the partial differential equations of electricity and heat conduction and the discrete formula of the finite element are also derived. According to the phase transition process of phase change materials, a crystalline-amorphous simulation model is also proposed in this paper to simulate the electrical and thermal properties and phase transition process of the resistive change unit. Simulations of the resistance change unit under single pulses with different amplitudes and widths as well as the simulations under continuous pulses are conducted in this paper. These results verify the characteristics of resistance change and can provide references for selecting the parameters of the resistance change units.